„Polskość” w słoweńskich przekładach Rozki Štefan / Polishness” in Slovenian translations by Rozka Štefan - Muszyńska, Anna (Przekłady Literatur Słowiańskich, 2009)
Rozka Štefan an outstanding specialist in Polish studies, translator and expert on Polish literature. She has devoted all her life to presenting Polish culture and literature to Slovenians. She has translated most of Polish Romantic literature into Slovenian (mainly Mickiewicz) and works of the most important contemporary poets rooted in „Polishness”, such as: Staff, Tuwim, Różewicz or Miłosz. Her translator selections (in the broad sense) are always tinted with a strategy of presentation of what is typically Polish, what is specific for the culture of the „country on the Vistula”; this is also proof that for a good translator there are no limits to convey the meaning. In 1999 an anthology of Polish love lyrics titled Antologija poljske ljubezenske lirike was published in Slovenia, in 2000 — her translation of Adam Mickiewicz’s Konrad Wallenrod followed by a selection of Tuwim’s poems (2001) — Julian Tuwim. The last three translation works by the 94 year old translator — covered by this paper — are perfect evidence of her translator consistency; they are a specific „summa” of her translating style, an essence of her translating perfectionism, both with respect to macro and micro choices in the plane of specific translated texts. Their common trait is her strategy of presentation of the „Polishness”.